Manifestations of ocular irritation after pterygium surgery with sutured conjunctival autograft - Molham A. Elbakary; Reham R. Shabana; Heba M. Shafik (African Vision and Eye Health, 2022)
Background: Ocular irritation remains the main disadvantage of the sutured conjunctival graft after pterygium excision. Evaluation of the severity of these manifestations can be helpful for better patient counselling about the expected postoperative course.